Space and Quantification in Languages of China - Xu, Dan (Springer, 2016)
This volume provides general linguists with new data and analysis on languages spoken in China regarding various aspects of space and quantification, using different approaches. Contributions by researchers from Mainland China, Hong Kong, Japan, Europe, the United States and Australia offer insights on aspects of language ranging from phonology and morphology to syntax and semantics, while the approaches vary from formal, historical, areal, typological, and cognitive linguistics to second language acquisition. After separate volumes on space and quantification in languages of China, the studies in this volume combine space and quantification to allow readers a view of the intersection of the two topics. Each article contributes to general linguistic knowledge while discussing a particular aspect of space or quantification in a particular language/dialect, offering new data and analysis from languages that are spoken in the same geographical area, and that belong to various language families that exist and evolve in close contact with one another.